Sleep disturbances and behavior in Smith-Magenis syndrome - Garayzábal, Elena; Hidalgo, Irene; Miranda de Souza, Ana Luiza Decanini [UNESP]; da Silva, Nathani Cristina [UNESP]; Giacheti, Celia Maria [UNESP]; Pinato, Luciana [UNESP] (Elsevier, 2022)
Background: The Smith-Magenis syndrome (SMS) shows a collection of neurodevelopmental problems including mild to moderate intellectual disability, change-related anxiety, impulsivity, speech delay, Attention-Deficit/Hyperactivity Disorder (ADH) and sleep disturbances. Sleep disorders, when present, have been treated in several populations with consecutive improvements in cognitive and behavioral aspects. Aims: To better understand the existing relationships between sleep disturbances and behavioral problems in SMS syndrome this study describes the sleep and behavior problems in the SMS and explores the possible relation between both. Methods and procedures: 17 individuals with SMS (50% males; 11.2 ± 4.9 years old) and 12 individuals with typical development (50% male; 11.1 ± 4.4 years old) were investigated using the Sleep Disturbance Scale for Children and the Child Behavior Checklist. Results: A high percentage (60%) of individuals with SMS have an indication of sleep disorders, being the most frequent disorders the sleep-wake transition disorders, and disorders of initiating and maintaining sleep with sleep latency higher than acceptable and total sleep time below acceptable. More than 94% of the SMS group presented clinical or borderline scores on the total behavioral problems scale. The most common behavioral problems were Externalizing Problems, Thought and Attention, ADH and Aggressive problems. There was a positive correlation between disorders of initiating and maintaining sleep, sleep-wake transition disorders, disorders of arousal, disorders of excessive somnolence and behavioral problems. Conclusions and implications: The worse the sleep disturbances investigated, the more severe the behavioral problems characteristics reinforcing the importance to address the sleep problems in the treatment of SMS individuals.
Keywords: Behavior; Neurodevelopmental disorder; Sleep; Smith Magenis syndrome